Why be Moral in a Virtual World? - McMillan, J; King, M (Oxford Uehiro Centre for Practical Ethics, 2017)
This article considers two related and fundamental issues about morality in a virtual world. The first is whether the anonymity that is a feature of virtual worlds can shed light upon whether people are moral when they can act with impunity. The second issue is whether there are any moral obligations in a virtual world and if so what they might be. Our reasons for being good are fundamental to understanding what it is that makes us moral or indeed whether any of us truly are moral. Plato grapples with this problem in book two of The Republic where Socrates is challenged by his brothers Adeimantus and Glaucon. They argue that people are moral only because of the costs to them of being immoral; the external constraints of morality. Glaucon asks us to imagine a magical ring that enables its wearers to become invisible and capable of acting anonymously. The ring is in some respects analogous to the possibilities created by online virtual worlds such as Second Life, so the dialogue is our entry point into considering morality within these worlds. These worlds are three dimensional user created environments where people control avatars and live virtual lives. As well as being an important social phenomenon, virtual worlds and what people chose to do in them can shed light on what people will do when they can act without fear of normal sanction. This paper begins by explaining the traditional challenge to morality posed by Plato, relating this to conduct in virtual worlds. Then the paper will consider the following skeptical objection. A precondition of all moral requirements is the ability to act. There are no moral requirements in virtual worlds because they are virtual and it is impossible to act in a virtual world. Because avatars do not have real bodies and the persons controlling avatars are not truly embodied, it is impossible for people to truly act in a virtual world. We will show that it is possible to perform some actions and suggest a number of moral requirements that might plausibly be thought to result. Because avatars cannot feel physical pain or pleasure these moral requirements are interestingly different from those of real life. Hume’s arguments for why we should be moral apply to virtual worlds and we conclude by considering how this explains why morality exists in these environments.